MEMBANDINGKAN SUMBER VOLATILITAS PASAR SAHAM KONVENSIONAL DAN PASAR SAHAM SYARIAH DI INDONESIA - Permana, Fikri C; Rodoni, Ahmad (FEB-UP Press, 2025)
This study investigates the sources of volatility affecting the performance of Indonesia’s stock market, focusing on both the conventional Jakarta Composite Index (JKSE) and the Sharia-based Jakarta Islamic Index (JII). The analysis considers three groups of potential determinants: (a) global macroeconomic factors, proxied by Brent crude oil prices (BRENT) and gold prices (GOLD); (b) international financial market linkages, represented by the Dow Jones Industrial Average (DJIA); and (c) Indonesia’s domestic fundamentals, proxied by the Rupiah–U.S. dollar exchange rate (USDIDR) and 10-year government bond yields (INDO10). Employing stochastic econometric approaches, including a multibreak structural model and volatility models (ARCH/GARCH), this study utilizes daily data spanning from January 2, 2019, to May 31, 2022. The findings reveal that structural breaks are more frequent in the JKSE than in the JII. Moreover, the persistence of structural breaks in both indices following the declaration of the COVID-19 pandemic indicates that the crisis effects remained unresolved throughout the observation period. Furthermore, domestic fundamentals (USDIDR and INDO10) exert the strongest influence on volatility in both indices, while the significant impact of BRENT and DJIA during certain break periods underscores the importance of global market dynamics.